Revitalization of urban streams. A holistic approach to the enhancement of an urban reach of the Pleichach River in the city of Würzburg, Germany. - Valladares, Valeria (My University, 2017)
This thesis focuses on the topic of urban stream river revitalization and how to maximize beneficial outcomes while minimizing potential risks when approaching this type of projects. It hypothesizes that through a holistic approach, based on the principles of ecosystem services, it is possible to develop and assess restoration strategies that find an adequate balance between ecology and human development. To sustain this assumption, a theoretical research was developed regarding river ecosystems and their processes, and how these have been affected by urbanization and human activities. This know-ledge base was complemented by a review of the Ecosystem Service Framework; used as a tool that enables uncovering the potentialities and risks involved in any given decision related to the management of natural resources for human benefit. Additionally, through an empirical analysis, best practice examples that successfully integrate ecological, social and flood protection objectives were studied. From this analysis, a set of fundamental strategies and principles common to all projects were abstracted in order to aid the development of future revitalization efforts. The knowledge acquired was applied to the case study of the revitalization of an urban reach of the Pleichach River, located in the city of Würzbug, Germany. Through a systematic design process, three options for restoration were proposed and assessed. It was concluded that all of these options represented ecological improvements when compared to the current status of the river, however, one of them offered a better balance between ecosystem services benefits and risks.
Keywords: Stadtentwicklungsplanung; Fluss; Stadtökologie; Landschaftsgestaltung; Ökosystem; Revitalisierung; Fallstudie; Renaturierung; Fließgewässer; Ufergestaltung